Pharmacological inhibition of fibroblast growth factor (FGF) receptor signaling ameliorates FGF23‐mediated hypophosphatemic rickets. (18th March 2013) - Wöhrle, Simon; Henninger, Christine; Bonny, Olivier; Thuery, Anne; Beluch, Noemie; Hynes, Nancy E; Guagnano, Vito; Sellers, William R; Hofmann, Francesco; Kneissel, Michaela; Graus Porta, Diana
Abstract Fibroblast growth factor 23 (FGF23) is a circulating factor secreted by osteocytes that is essential for phosphate homeostasis. In kidney proximal tubular cells FGF23 inhibits phosphate reabsorption and leads to decreased synthesis and enhanced catabolism of 1, 25‐dihydroxyvitamin D3 (1, 25[OH]2D3). Excess levels of FGF23 cause renal phosphate wasting and suppression of circulating 1, 25(OH)2D3 levels and are associated with several hereditary hypophosphatemic disorders with skeletal abnormalities, including X‐linked hypophosphatemic rickets (XLH) and autosomal recessive hypophosphatemic rickets (ARHR). Currently, therapeutic approaches to these diseases are limited to treatment with activated vitamin D analogues and phosphate supplementation, often merely resulting in partial correction of the skeletal aberrations. In this study, we evaluate the use of FGFR inhibitors for the treatment of FGF23‐mediated hypophosphatemic disorders using NVP‐BGJ398, a novel selective, pan‐specific FGFR inhibitor currently in Phase I clinical trials for cancer therapy. In two different hypophosphatemic mouse models, Hyp and Dmp1‐null mice, resembling the human diseases XLH and ARHR, we find that pharmacological inhibition of FGFRs efficiently abrogates aberrant FGF23 signaling and normalizes the hypophosphatemic and hypocalcemic conditions of these mice. Correspondingly, long‐term FGFR inhibition in Hyp mice leads to enhanced bone growth, increased mineralization, and reorganization of the disturbed growth plate structure. We therefore propose NVP‐BGJ398 treatment as a novel approach for the therapy of FGF23‐mediated hypophosphatemic diseases. © 2013 American Society for Bone and Mineral Research.